Analysis of DNA Methylation Profiles in Mandibular Condyle of Chicks With Crossed Beaks Using Whole-Genome Bisulfite Sequencing - Shi, Lei; Bai, Hao; Li, Yunlei; Yuan, Jingwei; Wang, Panlin; Wang, Yuanmei; Ni, Aixin; Jiang, Linlin; Ge, Pingzhuang; Bian, Shixiong; Zong, Yunhe; Isa, Adamu Mani; et al. (Frontiers in Genetics, 2021)
Crossed beaks have been observed in at least 12 chicken strains around the world, which severely impairs their growth and welfare. To explore the intrinsic factor causing crossed beaks, this study measured the length of bilateral mandibular ramus of affected birds, and investigated the genome-wide DNA methylation profiles of normal and affected sides of mandibular condyle. Results showed that the trait was caused by impaired development of unilateral mandibular ramus, which is extended through calcification of mandibular condyle. The methylation levels in the CG contexts were higher than that of CHG and CHH, with the highest methylation level of gene body region, followed by transcription termination sites and downstream. Subsequently, we identified 1,568 differentially methylated regions and 1,317 differentially methylated genes in CG contexts. Functional annotation analysis of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes showed that these genes were involved in bone mineralization and bone morphogenesis. Furthermore, by combining the WGBS and previous RNA-Seq data, 11 overlapped genes were regulated by both long non-coding RNA and DNA methylation. Among them, FIGNL1 is an important gene in calcification of mandibular condyle. Generally, because the affected genes play key roles in maintaining mandibular calcification, these changes may be pivotal factors of crossed beaks.